Assessment of nutritional interventions for modification of age-associated cognitive decline using a canine model of human aging - Araujo, Joseph A. (Kluwer Academic Publishers, 2005)
The present review focuses on the utility of a canine model in evaluating nutritional interventions for age-related cognitive dysfunction. Aged dogs demonstrate progressive cognitive decline with concurrent amyloid-beta pathology that parallels the pathology observed in aging humans. Dogs, therefore, provide a natural model of human pathological aging. We have and are in the process of evaluating several nutritional-based interventions aimed at preventing cognitive decline and brain aging. In a three-year longitudinal study, we examined the effects of a diet enriched with antioxidants and mitochondrial cofactors on several measures of cognition and brain aging. Compared to controls, aged dogs on the enriched diet demonstrated both short- and long-term cognitive benefits, as well decreased deposition of amyloid-beta protein. The diet also reduced behavioral signs associated with canine Cognitive Dysfunction Syndrome when assessed in veterinary clinical trials. We also have preliminary evidence suggesting a beneficial effect of a proprietary blend of docosahexaenoic acid and phospholipids on both cognitive and physiological measures. Collectively, our data indicate (1) that the dog, either in the laboratory or in the clinic, provides an important tool for assessing nutritional interventions and (2) that combination interventions aimed at several mechanisms of pathological aging may prove more effective than single nutritive components in human trials.